Material distribution network planning and design based on equivalent logistics quantity. (14th June 2023) - Fan, Jie; Wang, Chuangjian; Zuo, Ying; Xiang, Feng
The problems to be solved in material distribution can be summarised into two aspects: providing the quantity of materials needed for production and reducing logistics cost. By studying the expression form of the distribution quantity in the distribution process, this paper transformed the distribution demand into the logistics quantity, made an in-depth analysis of the distribution process, represented the change in logistics quantity of different materials with equivalent logistics quantities, and established the mathematical model and system dynamics model of the relationship between logistics quantity and distribution cost. Upon combining the experiment analysis of computer simulation, we finally designed a reasonable materials distribution scheme, which reduces the distribution cost and improves the efficiency of materials transportation.